2017
DOI: 10.1021/acs.jpcc.6b11426
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent in Situ Studies of Volatile Molecule Trapping in Low-Temperature-Activated Zr Alloy-Based Getters

Abstract: The activation process and the gettering mechanisms of Zr−Corare earth metal alloy getters were investigated. The evolution of the surface composition prior to and upon exposure to volatile molecules (O 2 , N 2 , CO 2 ) was monitored in situ using X-ray photoelectron spectroscopy under annealing conditions compatible with low processing temperature regimes. The thermally activated process of surface oxygen diffusion into the bulk was elucidated and found to involve an activation energy of 0.21 ± 0.02 eV in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 92 publications
(207 reference statements)
2
23
0
Order By: Relevance
“…3(a) shows an increase in C 1s concentration above 200 °C, which is attributed to hydrocarbon decomposition at the surface. (80) This decomposition is likely promoted by the catalytic effect of the cobalt content in this alloy. (96) The authors also reported in Ref.…”
Section: Thermal Activation Of Single and Alloy Getter Films In Uhvmentioning
confidence: 95%
See 4 more Smart Citations
“…3(a) shows an increase in C 1s concentration above 200 °C, which is attributed to hydrocarbon decomposition at the surface. (80) This decomposition is likely promoted by the catalytic effect of the cobalt content in this alloy. (96) The authors also reported in Ref.…”
Section: Thermal Activation Of Single and Alloy Getter Films In Uhvmentioning
confidence: 95%
“…However, in Ref. 80, the onset of activation was found at ~200 °C [ Fig. 3(a)] instead of about 300 °C for the co-evaporated Zr 48 Co 52 film (Fig.…”
Section: Thermal Activation Of Single and Alloy Getter Films In Uhvmentioning
confidence: 96%
See 3 more Smart Citations